MALDI-TOF MS as a tool for the identification of Vibrio alginolyticus from Perna perna mussels (Linnaeus, 1758) - Bronzato,Greiciane F. (2018)
ABSTRACT: Vibrio species are ubiquitous in aquatic environments, including coastal and marine habitats. Vibrio alginolyticus is an opportunistic pathogen for fish, crustaceans and mussels and their identification by biochemical tests may be impaired due their nutritional requirements. The study used Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) to identify 49 Vibrio spp. isolates associated with mussels (Perna perna) from different locations along the Rio de Janeiro coast. The rpoA gene was used as a genus-specific marker of Vibrio spp. and was positive in all 209 isolates. MALDI-TOF MS confirmed 87.8% of V. alginolyticus when compared to the results of the biochemical tests. Four isolates were identified as Shewanella putrefaciens (8.16%) and one was identified as V. parahaemolyticus (2.0%). Just one isolate was not identified by this technique (2.0%). The pyrH sequencing confirmed 75% of the proteomic technique results. MALDI-TOF MS is an excellent option for characterization of bacterial species, as it is efficient, fast and easy to apply. In addition, our study confirms its high specificity and sensitivity in these marine bacteria identification.